Translanguaging Pedagogies in an ESP Course: A Case in Indonesia - Triastuti, Aan; Nurkamto, Joko; Sumardi, Sumardi (VELES Voices of English Language Education Society, 2023)
This study investigates into the implementation of translanguaging pedagogy within Indonesian English for Specific Purposes (ESP) classrooms. In Indonesia, where multilingualism is prevalent, there is a growing trend to integrate local languages, such as Indonesian and Javanese, into educational contexts. This approach, which values and purposefully employs students' first languages (L1s), has been increasingly adopted by teachers. The research aims to explore Indonesian ESP teachers' perspectives on translanguaging and its application in their teaching practices. Through a qualitative case study, this paper examines how translanguaging facilitates communication, enhances teacher-student relationships, and aids in the processing of educational material. It also investigates potential resistance to monolingual pedagogies and the constructive use of translanguaging to further educational objectives. Data were gathered via semi-structured interviews with five ESP teachers and through classroom observations. The findings highlight the positive role of translanguaging in education. Teachers reported that translanguaging aids in knowledge construction, boosts vocabulary comprehension, strengthens interactions between teachers and students, and fosters a comfortable and engaging learning environment. These insights underline the importance of developing translingual strategies, encouraging teachers to incorporate students’ complete linguistic repertoire in their teaching. This approach not only facilitates English language learning but also acknowledges and leverages the linguistic diversity in Indonesian classrooms.